2020
DOI: 10.1101/2020.10.23.20218297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived Risk and Distress related to COVID-19: Comparing Healthcare versus non-Healthcare Workers of Pakistan

Abstract: Background Healthcare workers (HCWs) find themselves susceptible to contracting COVID-19 or being the source of exposure for their family members. This puts them at a high risk of psychological distress which may compromise patient care. In this study we aim to explore the risk perceptions and psychological distress between HCWs and non-healthcare workers (NHCWs) in Pakistan. Methods A cross-sectional study was conducted in Pakistan using an online self-administered questionnaire. Respondents were categorize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This is in line with the assumption that negative perceptions of individuals negatively affect business outcomes when the employee believes the environment as inappropriate for work. Thus, this confirms the negative psychological and physical effects developed by the health staff dealing with patients of Covid-19 in the health sector (see: Abid et al, 2020;Flesia et al, 2020;Zandi et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is in line with the assumption that negative perceptions of individuals negatively affect business outcomes when the employee believes the environment as inappropriate for work. Thus, this confirms the negative psychological and physical effects developed by the health staff dealing with patients of Covid-19 in the health sector (see: Abid et al, 2020;Flesia et al, 2020;Zandi et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Our results show a positive impact of Covid-19 on perceived stress experienced by medical workers dealing with Covid-19 virus. The nature of this disease is frightful enough to make medical workers stressed and anxious while dealing with it directly in workplace (Abid et al, 2020 ; Qureshi et al, 2020 ). The pandemic has caused stress among medical workers both at work and off work, especially, when they are conscious of the fact that there are higher chances that they might not only contract the virus but may also become the source of transmitting it to their immediate family members (see: Nanjundaswamy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived JS at the time of the COVID-19 outbreak in China has been linked with psychological health and emotional wellbeing [ 17 ], psychological impact [ 18 ], level of knowledge, attitude, practice [ 19 ], employees’ commitment [ 20 ], and psychological distress [ 21 ]. However, we identified that most of the existing studies have been limited to the sources, discovery or diagnosis of stress.…”
Section: Introductionmentioning
confidence: 99%